2010
DOI: 10.1021/jf100135h
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Nanoparticles Improve the Physicochemical Properties of Curcumin and Effectively Enhance Its Antioxidant and Antihepatoma Activities

Abstract: Curcumin (CUR), a natural polyphenol isolated from tumeric ( Curcuma longa ), has been documented to possess antioxidant and anticancer activities. Unfortunately, the compound has poor aqueous solubility, which results in poor bioavailability following high doses by oral administration. To improve the solubility of CUR, we developed a novel curcumin nanoparticle system (CURN) and investigated its physicochemical properties as well as its enhanced dissolution mechanism. Our results indicated that CURN improved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
146
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(165 citation statements)
references
References 27 publications
(32 reference statements)
17
146
0
2
Order By: Relevance
“…This suggested that the DPPH scavenging activity of Cur NPs in CPH was stronger than that in NaCas, and was comparable with that of free Cur in DMSO. Similar results on the improved antioxidant activity of Cur after its complexation with colloidal particles such as b-casein, lecithins and PVP also have been reported (Pan et al 2013;Takahashi et al 2009;Yen et al 2010). These results may be attributed to the homogeneous distribution of NPs in the reaction medium, and the large surface area resulted from the nanometer-sized structures could facilitate the reactions of Cur with free radicals.…”
Section: Antioxidant Activity Of Cur Npssupporting
confidence: 71%
See 1 more Smart Citation
“…This suggested that the DPPH scavenging activity of Cur NPs in CPH was stronger than that in NaCas, and was comparable with that of free Cur in DMSO. Similar results on the improved antioxidant activity of Cur after its complexation with colloidal particles such as b-casein, lecithins and PVP also have been reported (Pan et al 2013;Takahashi et al 2009;Yen et al 2010). These results may be attributed to the homogeneous distribution of NPs in the reaction medium, and the large surface area resulted from the nanometer-sized structures could facilitate the reactions of Cur with free radicals.…”
Section: Antioxidant Activity Of Cur Npssupporting
confidence: 71%
“…The methodology of DPPH scavenging activity measurement was carried out following Yen et al (2010) with modifications. Briefly, free Cur in DMSO and Cur NPs in CPH and NaCas were prepared at multiple concentrations (10-50 lg/mL).…”
Section: Dpph Scavenging Activitymentioning
confidence: 99%
“…Figure 5 lists the FT-IR spectrums of CUR, lyophilized CUR-free and -loaded micellar particles. Peak of free CUR at 3508 cm À1 was assigned to the stretching vibration of phenolic hydroxyl group (Yen et al, 2010;Xie et al, 2011). In comparison with the blank micellar particles' C¼O stretching vibration bond at 1729 cm À1 , the C¼O absorption band blue shift of CUR micellar particles took place (Figure 5).…”
Section: Characterization Of Micellesmentioning
confidence: 99%
“…H-NMR spectrum of tetra-hydroxy MPEG (A) and LDMP (B). DOI: 10.3109/10717544.2014.901436 X-ray diffraction measurement was also used to confirm the physical state of CUR in micelles, because the exitential state of drug in the copolymeric materials of micelles was important to the drug release characteristics (Donsi et al, 2010;Yen et al, 2010). XRD spectra of CUR, CUR-free micelles and CUR micelles are shown in Figure 6.…”
Section: Characterization Of Micellesmentioning
confidence: 99%
“…Further, the assessment of its antioxidant activity in fruit juice matrix shows antioxidant activity did not get influenced by matrix effect. Previous studies have also shown that DPPH radical scavenging activity of curcumin nanoparticulate systems was superior to its free form (Yen et al 2010) Anti-lipid peroxidation (TBARS) assay…”
Section: Thermal Characterization (Dsc)mentioning
confidence: 99%